Observing student’s situational interest based on the implementation of reward and punishment in physical education - Friskawati, Gita Febria; Widaningsih, Sri; Illahi, Rizki (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
This study aims to identify how rewards and punishment influence the situational interests of high school student’s, observed from providing individual or group learning tasks in physical education. In addition, the method adopted was factorial 2 x 2 research design with the implementation procedure involved Experimental Counterbalance. Furthermore, samples were taken using cluster random sampling in two classes, including students of class XI IPA 1 and XI IPA 4, with a total number of 72 people, both male and female. Subsequently, data retrieval required the use of situational interest scale questionnaire by Chen et al (2007), indicating a coefficient of validity and reliability of 0.718. Therefore, the findings show significant rewards and punishment, in contrast with those that were not given, while, the learning task as individuals or group did not significantly improve situational interest.